ADMINISTRATIVE LIABILITY IN THE SPHERE OF CUSTOMS REGULATION: THEORETICAL AND LEGAL FOUNDATIONS, QUALIFICATION, AND INTERDISCIPLINARY CONNECTIONS - Kravets , Maryna (Collection of scientific papers «ΛΌГOΣ», 2025)
The process of legal qualification in the area of customs-related administrative liability requires precision, consistency, and alignment with the structure of legal norms. A key challenge is the procedural complexity of applying Article 468 of the Customs Code of Ukraine, which governs the classification of customs violations within simplified customs control zones [1, p. 38-42]. A thorough retrospective review of relevant legal provisions since Ukraine’s independence reveals shifting standards in the administrative regulation of customs enforcement [2, p. 82-85].